Role of Self Care Practices and Denture Maintenance in Oral Health - Shetty, Mallika S; Shenoy, Rekha P; George, Vinu Thomas (Journal of Orofacial Research, 2014)
Background: Edentulous patients seek treatment to restore their oral function and esthetics, so that they can eat and speak more easily and feel better about themselves. The dental prosthesis helps replacement of teeth and restores oral function and esthetics. For the success of the treatment and acceptance ofthe prosthesis, maintenance of the prosthesis by the patient is very important. The authors’ objective in this study was to analyze how selfcare practices in terms of oral hygiene habits, maintenance of dentures, type of prosthesis are affected by age, gender and education level. Materials and methods: The authors developed a written oral health questionnaire and administered it to 586 individuals in dental care centres in Mangalore, South India. They ollected demographic information as well as data on oral hygiene practices and prosthetic status. The data was compared using Chi-squared test and the value of p < 0.05 was considered statistically significant. Results: The sample surveyed consisted of 586 participants (257 males and 329 females) of which 76 (13.0%) were with complete dentures, 312 (53.3%) with Fixed Prosthesis, 165 (28.2%) with Removable Partial dentures and 33 (5.5%) had a combination of the fixed and removable prosthesis. The study showed that denture cleansing habits, Oral hygiene habits, how prosthesis was worn, type of prosthesis were significantlyassociated with age and educational status of the subjects. Conclusion: Intensive population-directed strategies for oral health education should be developed in order to improve the oral hygiene practices, denture cleansing habits in the entire population.